HUBUNGAN KEKERABATAN FENETIK IKAN KERAPU SUB FAMILI EPINEPHELINAE DI KEPULAUAN TIWORO KABUPATEN MUNA PROVINSI SULAWESI TENGGARA - , LA ODE ABDUL RAJAB NADIA; , Drs. Trijoko, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Groupers are members of reef fish of the subfamily Epinephelinae that until recently their identity is still being studied due to its diversity and its high potential in waters. One of the distributional regions of groupers that remain potential is the Tiworo islands. The aims of this research to discover the diversity of species of groupers and to study their phenetic relationship. The research was conducted in the period of January to July 2012. The research procedures include: a) the collection of specimens (3-5 individuals/species) at the site of research using fish traps (bubu and fishing rods), b) measurement of water quality parameters, c) determination of Operational Taxonomy Units (OTU's) representing every single species, d) selection of character, consists of 62 characters (morphology and anatomy), e) phylogenetic interpretation based on teeth character of the specimens. Data analysis was conducted using Numerical Taxonomy and Multivariate Analysis System/NTSys-pc software. The results species identification showed 19 species of groupers that belongs to the 6 genus: Anyperodon (species of A.leucogrammicus), Cephalopholis (species of C.argus, C.boenak, C.cyanostigma, C.miniata, C.spiloparaea, C.urodeta), Epinephelus (E.areolotus, E.coralticola, E.fuscoguttatus, E.merra, E.ongus, E.quoyanus, E.retauti, E.sexfasciatus), Gracilaria (species of G.Albomarginata), Pelctropomus (species of P.oligacanthus, P.pessulferus) and Variola (V.albimarginata). Phenetic relationship analysis yielded grouper species grouping into two big groups: the first group I consisted of the genus Anyperodon, Cephalopholis and Epinephelus, and group II consisted of the genus Gracilla, Variola and Plectropomus. Phylogenetic interpretations on teeth character indicated that the species of A.leucogrammicus was categorized as primitive, species of C.boenak and C.spiloparaea as have been developing and other species are categorized as developed. Species of groupers found at the site of research vary widely and the environmental characteristics of its waters supported the existence of groupers.